2018
DOI: 10.1039/c7ra12520h
|View full text |Cite|
|
Sign up to set email alerts
|

SNHG5 promotes proliferation and induces apoptosis in melanoma by sponging miR-155

Abstract: Melanoma is the most common malignancy of skin cancer. Small nucleolar RNA host gene 5 (SNHG5), a long non-coding RNA (lncRNA), has been demonstrated to be upregulated in tumor tissues and cells of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…Additionally, SNHG5 expression was upregulated in bladder cancer, and SNHG5 knockdown repressed cell growth and induced apoptosis in a p27-dependent manner 14. In the current study, SNHG5 expression was found to be upregulated in melanoma tumor tissues and cell lines, and correlated with advanced pathological stages, consistent with a previous study 16…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, SNHG5 expression was upregulated in bladder cancer, and SNHG5 knockdown repressed cell growth and induced apoptosis in a p27-dependent manner 14. In the current study, SNHG5 expression was found to be upregulated in melanoma tumor tissues and cell lines, and correlated with advanced pathological stages, consistent with a previous study 16…”
Section: Discussionsupporting
confidence: 91%
“…These data uncovered that SNHG5 exerted functions as an oncogene in melanoma by sponging miR-26a-5p. Coincident with our results, Yan et al validated that SNHG5 knockdown suppressed proliferation and facilitated apoptosis in melanoma cells by serving as a molecular sponge of miR-155 16…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…to exert oncogenic roles in colorectal cancer, melanoma, bladder cancer, and hepatocellular carcinoma (Damas et al, 2016;Ma, Xue, Zeng, & Qiu, 2018;Yan et al, 2018) while inhibits gastric cancer evolution (Zhao et al, 2016). Besides, we reported associations between expression levels of this lncRNA and histological grade, which is in line with findings in hepatocellular carcinoma (Y.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, there existed a sponged regulation between lncRNA XIST and miR-155 within breast cancer cells, 13 which provoked a speculation that lncRNA XIST might be implicated in AS aetiology via its sponging miR-155. Concerning another lncRNA studied here, the lncRNA SNHG5 was also suggested to negatively regulate miR-155 expression within melanoma cells, 14…”
Section: Introductionmentioning
confidence: 84%